The Dark castle - Kawasaki, Masatsugu; Kikuchi, Harou; Kitamoto, Isao.; Tamai, Isao.; CCTV (China).; NHK Enterprises, Inc. (Japan). ([S.l.] NHK, 1990)
Discover the ghost castle of Khara-Khoto, 250 miles from the oasis of Giu-Chang near the Quilian mountains in the Gobi Desert. The legendary lost city was obliterated by Genghis Khan, who exterminated the Tangut people who built it. Burried by the Gobi sands, it was unearthed by the Russian explorer Koslov, who took its artworks to the Russian Art Museum to the Hermitage. The castle believed by the Chinese to have been cursed has not been entered for over 50 years. It stands near the Russian-Chinese border and it is in the sensitive military zone of the Chinese army.
VHS.
Edited by Hiroyuki Shoji; Narrated by Graham Webster.
Keywords: Castles -- China; Silk Road; China -- Antiquities; China -- Description and travel; China -- History